O discurso sobre a internacionalização das universidades brasileiras - Nakamura, Ádria Ramos Lustosa (2021)
The idea of internationalization has aroused the interest of university institutions, national governments and international organizations involved with higher education (DE WIT, 1998; DE WIT et al., 2017; KNIGHT, 2012) since the decade of 1990. This interest has been consolidated as a recurring object of scientific investigation (BERRY; TAYLOR, 2014; DOLBY; RAHMAN, 2008; KEHM; TEICHLER, 2007; YEMINI; SAGIE, 2015) in order to broaden the understanding of a complex social phenomenon that involves different motivations, stages, forms of manifestation and consequences (KNIGHT, 2004; 2015). From the moment universities enabled the collective construction of regional knowledge that would allow them to critically face the challenges posed to societies in a phase of globalized economy, researchers and their institutions began to think outside national boundaries and took on transnational/international approaches. In this context, one nation stands out: the American, the most influential among the large economies and, consequently, its official language, the English language, which is also reflected in the scope of research and extension within universities. Thus, there is a need to train university students, who are not yet proficient in the English language, to act in this context. In this thesis, we present some programs and actions that have been implemented within Brazilian universities in recent years (2011-2018) in relation to internationalization. Our analysis will focus on the discursive construction of Internationalization in government documents that formalized internationalization programs for Brazilian universities, a specific enunciative series from an archive of public policies in education in Brazil. They are: a decree and four ordinances from the Ministry of Education (MEC) dealing with the institutionalization of the CsF, IsF and Languages without borders programs, and two more reports, one being the Capes report on the internationalization of Brazilian universities and the other a national report of English proficiency in the IsF program, and, finally, the Capes-Print Public Notice, totaling eight documents. For this, we will discuss the notions of archival and interpretation and will take, as the main categories of our analysis, the said and unsaid, subject-positions, discursive formations, discursive memory, meaning and interdiscourse effects, among other categories related to Discourse Analysis with a Pecheuxtian basis. After the discursive analysis of these documents, we do not seek to present a meaning, a discursive subject or a subject-position; on the contrary, we aim to understand the effects of the emergence of the internationalization of Brazilian universities in public policies of internationalization from the discursive functioning of the syntagma "internationalization" in the documents that make up our corpus, knowing that, within the theoretical-methodological perspective of Discourse Analysis (AD), discourse is not a mere transmission of information, but a process of production of meaning effects that constitutes “in the functioning of language, which relates subjects and senses affected by language and history” (ORLANDI, 2013 p .21).